Barriers to the adoption of waste-reducing eco-innovations in the packaged food sector: A study in the UK and the Netherlands. (20th January 2020) - Simms, Christopher; Trott, Paul; Hende, Ellis van den; Hultink, Erik Jan
Abstract: The food processing sector has a considerable environmental impact, due to large volumes of food and packaging waste. Eco-innovations present an important opportunity to reduce this impact. Yet, initial insights suggest that new technologies face considerable challenges to their adoption. The eco-innovation adoption literature has overlooked the food processing sector. The purpose of this paper is to examine the barriers inhibiting the adoption of waste reducing eco-innovations in the food processing sector. We present four detailed case studies of new technologies at different stages of adoption in the UK and Netherlands. The findings reveal ten barriers to the adoption of waste reducing technologies in the food processing sector. The barriers identified include concerns over the influence of technologies on the product's characteristics, its retailing, and a perceived lack of consumer demand. These barriers arise from the powerful influence of retailers within the food supply chain, the influence of technologies on in-store point of sale displays, and the need for distribution trials. We conclude that the adoption of new technologies requires simultaneous acceptance by both food processor and retailers. The paper provides recommendations for policy makers and innovation managers to increase the adoption and diffusion of waste reducing technologies in the food processing sector, as well as implications for future research. Highlights: Interconnected barriers are identified across key members of the food supply chain. Specific characteristics of waste reducing eco-technologies impede their adoption. Retailers role in the adoption of waste reducing technologies is uncovered. Policy action is required to promote adoption at each level of the supply chain.